Quality in the Music Applications: Case Study in Spotify, ITunes and JOOX - Rachmat, Timotius Agus; Nawangwulan, Irma M; Anantadjaya, Samuel PD; Samuel, DC Ethan; Lahuddin, Abdul Haris; Samuel, Daniella Christy Eryn (Sekolah Tinggi Manajemen IPMI, 2025)
In the several years, streaming services have been under the spotlight by disrupting traditional media consumption platforms. The music industry is one of the most heavily impacted by the existance of streaming services. The aim of this paper is to understand the customer’s expectation for a music application and how far that is being full filled. Through the SERVQUAL scale, the customer’s expectation and the perception of the applications’ services quality will be analysed and the perceived quality of music streaming platform, Spotify, and digital music platform, iTunes will be compared